Sensitive dual-labeled electrochemical aptasensor for simultaneous detection of multi-antibiotics in milk. (1st July 2021) - Li, Falan; Wu, Yanfang; Chen, Dongfei; Guo, Yemin; Wang, Xiangyou; Sun, Xia
Abstract: In this work, a dual-labeled multiple aptasensor that can simultaneously detect multiple antibiotics was constructed, with kanamycin (KAN) and tobramycin (TOB) used as the model analytes. The aptasensor reported here featured three key elements, namely the RNA-based aptamer strands, semiconductor quantum dots (QDs), and gold nanoshells (AuNSs). Due to the high-affinity pairing between streptavidin (SA) and biotin (Bio), the two biotinylated aptamers (kanamycin aptamer, KAP; tobramycin aptamer, TAP) responsible for the specific recognition of KAN and TOB were conjugated to SA-coated cadmium sulfide (CdS) and lead sulfide (PbS) QDs, respectively for the syntheses of KAP-Bio-SA-CdS and TAP-Bio-SA-PdS composites. Moreover, the AuNSs had a very high loading efficiency for the as-prepared two composites on the gold electrode surface due to their outstanding surface-area-to-volume ratio. In the presence of target antibiotics, CdS and PbS QDs were released from AuNSs followed by dissolution into their respective metal ions for stripping analysis by differential pulse voltammetry (DPV). As a result, intensified signals from DPV peaks were obtained due to the large amount of the metal ion labels dissolved in the solution. The devised aptasensor exhibited wider detection linear range (KAN, 1–4 × 10 2 nM; TOB, 1–1 × 10 4 nM) and lower detection limits (KAN, 0.12 nM; TOB, 0.49 nM) compared to the previously reported sensors. Furthermore, the detection of KAN and TOB spiked in milk samples was successfully demonstrated. Therefore, the proposed aptasensor provides a novel sensitive platform for multi-antibiotics detection. Highlights: A dual-labeled multiplex aptasensor for multiple antibiotics was fabricated. The different aptamers were labeled with different metal ions. Core-shell structure AuNSs were prepared. KAN and TOB detection in real milk exhibited good reliability.